DERIVATIONAL PROCESSES OF THE PROTO-SLAVIC ROOT *MER - IN MACEDONIAN LANGUAGE (Journal of Contemporary Philology, 2020)
In the recent years the employees of the Research Center for Areal Linguistics at the Macedonian Academy of Sciences and Arts have been working on a new approach for the description of the word formation system in the Macedonian language. The approach consists of researching groups of lexemes derived from the same root attested in the Proto-Slavic language. According to Markovikj and Topolińska (Марковиќ и Тополињска 2019), one of the most important processes that presents the systematic transfer of information from the semantic continuum to the lexicon of the language is the semantic derivation. This process allows the observation of the associative sequences, which retain the basic, initial semantic components, transmitted from the man and from the real physical world to the human mental world. The research is based on the anthropocentric-spatial language theory which helps to analyse how the basic semantic component embedded in some verbal roots representing basic human conditions and activities can transfer and rise through evolution of the conceptualization. In this paper, the author analyzes the formal and the semantic derivation of the Proto-Slavic root *mer- in the Macedonian language, which has developed several variations (*mer-, *mor-, *mar-, *mьr-) since the Proto-Slavic period. Its embedded semantic component is “stop living (existing)”.
Keywords: semantic derivation; formal derivation; Macedonian language; word formation nest; anthropocentric-spatial language theory